Fault isolation technique for decentralized survivable communication network systems via regions and paths - Nethravathi B; Kamalesh V N (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The rapid continuous growth of communication networks in size, complexity and dependencies, makes them extremely challenging to maintain the survivability of the complete large network.  The complexity may be due to advance voice and video services like IP TVs, IP telephony, video streaming which demands high reliability and survivability. Network management has become a great challenge as Faults are expected only in these complex networks. Once a failure is detected, the next step in the diagnosis is fault isolation which locates the source of that failure. The necessitate of decentralized diagnosis is justified by various applications, like spacecrafts.  This article presents model based fault isolation technique using a graph theoretical concepts, regions and paths for decentralized communication networks.